Big data analytics and knowledge discovery : 22nd International Conference, DaWaK 2020, Bratislava, Slovakia, September 14-17, 2020, Proceedings /: 22nd International Conference, DaWaK 2020, Bratislava, Slovakia, September 14-17, 2020, Proceedings. ([2020]) - Unknown
No abstract available